An intellectual capital maturity model (ICMM) to improve strategic management in European universities. Issue 2 (13th April 2015) - James Guthrie; Associate Professor John Dumay, Professor; Secundo, Giustina; Elena- Perez, Susana; Martinaitis, Žilvinas; Leitner, Karl-Heinz
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The public sector is one of the least addressed areas of intellectual capital (IC) research. Universities are an interesting area of investigation because they are considered critical players in the knowledge-based society. The purpose of this paper is to develop a more general, flexible and comprehensive "IC Maturity Model" for Universities (ICMM), a framework for defining and implementing IC measurement and management approaches, as part of the whole strategic management of universities. Thus, the ICMM proposes a staged framework to initiate a step-by-step change within a university based upon its current level of IC management maturity. The different steps of maturity might be an answer to cope with the huge diversity of European universities, some of which have strong managerial orientation, while others follow collegial forms of governance. Design/methodology/approach – The research approach is based on what has been called the "third stage" of IC research (Dumay and Garanina, 2013), focused on the practices of IC approaches rather than on its theoretical conceptualisation. The ICMM has been developed under the "Quality Assurance in Higher Education through Habilitation and Auditing" project framework, initiated by the Executive Agency for Higher Education and Research Funding of Romania (EUFISCDI). Three Mutual Learning Workshops (MLWs) were organised as a mean to bring together 15 international experts and practitioners to share their views and experience on IC reporting and setting up task forces. Findings – An ICMM, which is a flexible model of implementing IC approaches within public universities, is developed. The ICMM provides a theoretical continuum along which the process of maturity can be developed incrementally from one level to the next, moving from IC data collection, awareness of IC, adjustment of IC specific indicators, measurement of IC, reporting of IC, interpretation and decision making, strategy and planning. Research limitations/implications – Future research needs to conduct empirical studies in universities to generalise the effectiveness of the ICMM model and guidelines for implementation. Practical implications – The ICMM provides a staged framework to initiate a step-by-step change within a university based upon its current level of IC management maturity and its IC value creation dynamics. It allows universities to follow different paths, not necessarily a linear sequence. Originality/value – Although several methods for IC measurement and management exist, most of these cannot accommodate the trade-off between the comparability aims and the efforts to capture the institution's uniqueness when designing an IC model.